2017
DOI: 10.3390/ijms18040690
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Licochalcone C on the Regulation of PI3K/Akt/eNOS and NF-κB/iNOS/NO Signaling Pathways in H9c2 Cells in Response to LPS Stimulation

Abstract: Polyphenols compounds are a group molecules present in many plants. They have antioxidant properties and can also be helpful in the management of sepsis. Licochalcone C (LicoC), a constituent of Glycyrrhiza glabra, has various biological and pharmacological properties. In saying this, the effect of LicoC on the inflammatory response that characterizes septic myocardial dysfunction is poorly understood. The aim of this study was to determine whether LicoC exhibits anti-inflammatory properties on H9c2 cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 46 publications
2
33
0
1
Order By: Relevance
“…31 Among these reported polyphenols, LCC has been reported to exhibit various pharmacological effects, such as the PTP1B enzyme inhibitory activity, 32 attenuation of inflammatory response, 7 cardio-protective effect, 7,33 and apoptosis, 10 but their mechanisms of action remain elusive. Furthermore, according to Franceschelli et al, 34 LCC did not show cytotoxic activity on cardiomyocyte cell line, H9c2 cells even at a concentration 250 μM. We investigated whether LCC could suppress cell growth and induce apoptosis through the regulation of the JAK2/ STAT3 pathway in OSCC cell lines (HN22 and HSC4).…”
Section: Discussionmentioning
confidence: 90%
“…31 Among these reported polyphenols, LCC has been reported to exhibit various pharmacological effects, such as the PTP1B enzyme inhibitory activity, 32 attenuation of inflammatory response, 7 cardio-protective effect, 7,33 and apoptosis, 10 but their mechanisms of action remain elusive. Furthermore, according to Franceschelli et al, 34 LCC did not show cytotoxic activity on cardiomyocyte cell line, H9c2 cells even at a concentration 250 μM. We investigated whether LCC could suppress cell growth and induce apoptosis through the regulation of the JAK2/ STAT3 pathway in OSCC cell lines (HN22 and HSC4).…”
Section: Discussionmentioning
confidence: 90%
“…The high expression level of iNOS from both macrophage and cardiomyocytes could lead to the systemic and cardiac dysfunction in sepsis (Franceschelli et al, ; Ndongson‐Dongmo et al, ). That might be partly related to increased production of superoxide and the resulting increased level of oxidative stress (Neri, Riezzo, Pomara, Schiavone, & Turillazzi, ).…”
Section: Resultsmentioning
confidence: 99%
“…PI3K and its downstream effector, the serine/threonine kinase AKT/PKB, play a role in renal cellular survival or death . An LPS‐mediated‐AKT pathway was reported in different cell types, such as fibroblasts and neuroblastoma cells, which inhibits proapoptotic proteins, such as Bax . It was also demonstrated that NaB exerts antiapoptotic effects via the PI3K/AKT pathway on serum deprivation‐induced apoptosis in hepatic ischemia/reperfusion injured mice .…”
Section: Discussionmentioning
confidence: 99%